1992
DOI: 10.1073/pnas.89.12.5452
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Escherichia coli RuvA and RuvB proteins with synthetic Holliday junctions.

Abstract: The RuvA, RuvB, and RuvC proteins of Eseherichia coli are required for the recombinational repair of ultraviolet light-or chemical-induced DNA damage. In vitro, RuvC protein interacts with Holliday junctions in DNA and promotes their resolution by endonucleolytic cleavage. In this paper, we investigate the interaction of RuvA and RuvB proteins with model Holliday junctions. Using band-shift assays, we show that RuvA binds synthetic Holliday structures to form specific protein-DNA complexes. Moreover, in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
124
1

Year Published

1993
1993
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(137 citation statements)
references
References 21 publications
12
124
1
Order By: Relevance
“…In previous studies, RuvA and RuvB were shown to Directionality of RuvAB-mediated branch migration promote branch migration of Holliday junctions in vitro (Iwasaki et al 1992;Müller et al 1993;Parsons et al 1992;Parsons & West 1993;Tsaneva et al 1992b). The structure of the RuvAB-Holliday junction complex was analysed by electron microscopy and DNase I protection, which showed that the complex is tripartite, with RuvA sandwiched between two hexameric rings of RuvB (Hiom & West 1995;Parsons et al 1995a).…”
Section: Discussionmentioning
confidence: 91%
“…In previous studies, RuvA and RuvB were shown to Directionality of RuvAB-mediated branch migration promote branch migration of Holliday junctions in vitro (Iwasaki et al 1992;Müller et al 1993;Parsons et al 1992;Parsons & West 1993;Tsaneva et al 1992b). The structure of the RuvAB-Holliday junction complex was analysed by electron microscopy and DNase I protection, which showed that the complex is tripartite, with RuvA sandwiched between two hexameric rings of RuvB (Hiom & West 1995;Parsons et al 1995a).…”
Section: Discussionmentioning
confidence: 91%
“…The concerted actions of RuvA, RuvB and RuvC proteins complete the homologous recombination process by resolving the Holliday junctions into two recombinant duplex DNA molecules West 1997). RuvA and RuvB form a complex that promotes branch migration (Iwasaki et al 1992;Parsons et al 1992;Tsaneva et al 1992). In this reaction, RuvA specifically binds the junction and targets RuvB to it (Iwasaki et al 1992;Parsons et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…RuvA and RuvB form a complex that promotes branch migration (Iwasaki et al 1992;Parsons et al 1992;Tsaneva et al 1992). In this reaction, RuvA specifically binds the junction and targets RuvB to it (Iwasaki et al 1992;Parsons et al 1992). RuvB protein forms a hexameric ring (Stasiak et al 1994) and possesses an ATP-dependent helicase activity that provides the driving force for branch migration (Tsaneva et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical studies have shown that the RuvA and RuvB proteins interact with Holliday junctions to promote their movement along DNA, by a process known as branch migration (6)(7)(8). The RuvC protein resolves Holliday junctions by endonucleolytic cleavage (9,10).…”
mentioning
confidence: 99%
“…RuvA (22 kDa) and RuvB (37 kDa) each play a defined role in branch migration, with RuvA targeting RuvB to the Holliday junction (11,12). The selective binding of RuvA to junctions (7,11), the stimulation of RuvB's ATPase by RuvA/DNA (8), and observations which show that saturating concentrations of RuvB alone can promote branch migration (13) suggest that RuvB is the motor that drives strand exchange during branch migration, with RuvA playing an ancillary role (12). Further biochemical studies of RuvAB have revealed a DNA helicase activity that unwinds DNA with a 5'-to-3' polarity (14).…”
mentioning
confidence: 99%